Simple, fast and environmentally friendly method to determine ciprofloxacin in wastewater samples based on an impedimetric immunosensor - Lamarca, Rafaela Silva [UNESP]; Faria, Ricardo Adriano Dorledo De; Zanoni, Maria Valnice Boldrin [UNESP]; Nalin, Marcelo [UNESP]; Lima Gomes, Paulo Clairmont Feitosa De [UNESP]; Messaddeq, Younès [UNESP] (Royal Society of Chemistry (RSC), 2020)
In this study an impedimetric immunosensor was developed in order to determine ciprofloxacin (CIP) in wastewater samples, an emergent contaminant widely found in wastewater. To achieve this, an anti-ciprofloxacin antibody was immobilized on the surface of a printed carbon electrode. Then, the developed immunosensor was applied in wastewater samples from Université Laval residences (Québec, Canada) through the load transfer resistance (Rct) using [Fe(CN)6]3-/4- as a redox probe, and the average CIP concentration was found to be 2.90 × 10-4 μg mL-1. The observed Rct changes presented a linear relationship from CIP concentrations of 10-5 to 1.0 μg mL-1, with detection and quantification limits of 2.50 × 10-6 and 7.90 × 10-6 μg mL-1, respectively. The immunosensor presented high selectivity and repeatability, as well as a good recovery rate in wastewater samples (97%). Significant interference with other compounds was not observed. The proposed method requires only 30 μL of sample without the use of organic solvents or preceding sample preparation and/or extraction techniques. Moreover, the method is fast: only 20 min of incubation followed by 2 min of analysis time was sufficient to obtain the CIP concentration. The method's estimated cost is U$ 2.00 per sample.